2017
DOI: 10.1111/echo.13496
|View full text |Cite
|
Sign up to set email alerts
|

Loss of base‐to‐apex circumferential strain gradient: A specific pattern of Fabry cardiomyopathy?

Abstract: Loss of base-to-apex CS gradient may be a specific left ventricular deformation pattern of Fabry cardiomyopathy in patients with and without LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…For example, a pronounced base-to-apex LS gradient with preserved apical longitudinal strain has been shown to differentiate cardiac amyloid from other causes of LVH including FD [28, 29]. We found that there was no significant difference in base-to-apex LS gradient between FD patients and controls, similar to a prior study that evaluated strain using echocardiography [12].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For example, a pronounced base-to-apex LS gradient with preserved apical longitudinal strain has been shown to differentiate cardiac amyloid from other causes of LVH including FD [28, 29]. We found that there was no significant difference in base-to-apex LS gradient between FD patients and controls, similar to a prior study that evaluated strain using echocardiography [12].…”
Section: Discussionsupporting
confidence: 84%
“…Gruner et al found that GLS and GCS were reduced in FD patients with and without LVH, although there was a greater decrease in GLS among LVH positive patients [10]. Loss of base-to-apex CS gradient assessed by echocardiography has previously been reported in patients with FD [10, 12]. The current study confirms this finding using CMR feature tracking strain analysis, and provides additional information on the association of base-to-apex CS gradient with other CMR parameters including T1 mapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deformation imaging can also depict the typical pattern of distribution of lower longitudinal strain mainly involving the inferolateral segments of the LV. Moreover, several studies 47, 48 demonstrated that while longitudinal strain was impaired in both AFD and HCM ( Figure 9 ), circumferential strain was significantly lower in AFD than in HCM, in AFD patients with LV hypertrophy and in those without. Both studies demonstrated a loss of the base-to-apex circumferential gradient AFD patients, the gradient being significantly lower as compared to HCM patients.…”
Section: Challenges Of Imaging In LV Hypertrophymentioning
confidence: 94%
“…Whilst some studies have demonstrated a decrease in GLS this reduction is generally due to a regional decrease in strain in the basal inferolateral regions (Figure 8) [77,80,81]. Furthermore, the circumferential strain is also reduced in patients with AFD with a decrease in both the global circumferential strain and a loss of the normal base to apex gradient [77,80].…”
Section: Advanced Echocardiographic Imagingmentioning
confidence: 99%